Determining submarine dynamic cable stiffness and fatigue characteristics through physical testing - Thies, PR; Georgallis, G (American Society of Mechanical Engineers (ASME), 2024)
This is the author accepted manuscript. Offshore wind farms are moving into deeper waters, where fixed foundations are not economically viable, forcing the development of floating wind turbines. Recent global estimates by 4C Offshore expect a total of 14 GW of floating wind turbines to be installed by 2030, with another 40GW installation forecasted up to 2050. This will necessitate the manufacture, installation, and commissioning of thousands of floating wind platforms. Electricity will need to be exported from these installations, and therefore dynamic submarine power cables will be one of the most critical and exposed components, connecting the floating platform to static subsea export cables or floating export / production platforms. Dynamic submarine power cables must now have the ability to support increased loads caused by this move into deeper waters and the movement of the floating vessel or platform. They must also be able to tolerate fatigue associated with load changes that occur during their movement in the water column. The structural characteristics of dynamic power cables are often approximated through numerical modelling, and full-scale cable mechanical testing is essential for accurate measurement of key properties, including axial stiffness and bending stiffness. This paper presents a case study and characteristic results of a mechanical cable test campaign, quantifying cable stiffness and fatigue. The example illustrates the value of mechanical testing to better inform both global hydrodynamic models with cable properties and to better calibrate local finite element analysis tools.The paper is useful for researchers and practitioners concerned with the modelling, design and testing of submarine dynamic power cables. It is also useful for project investors and underwriters to better understand the assurance testing of cables as a critical component. European Union Horizon 2020 Engineering and Physical Sciences Research Council (EPSRC)